Desenvolvimento de carreadores lipídicos nanoestruturados para o encapsulamento de carvacrol : uma formulação promissora para o tratamento de leishmanioses - Galvão, Juliana Gouveia (2019)
Leishmaniasis is a neglected infectious disease caused by protozoa of the genus Leishmania. The current leishmaniasis treatment is expensive, usually causes adverse effects and it is ineffective for resistant leishmania strains. Therefore, molecules derived from natural products as the monoterpene carvacrol, has been attracted interest as promising anti-leishmania agents. However, the therapeutical use of carvacrol is limited due to its low aqueous solubility, ease oxidation and volatilization. Thus, the development of nanostructured lipid carriers was proposed in the present study as a promising nanotechnology strategy to overcome these limitations and enable the use of carvacrol in leishmaniasis therapy. Firstly, it was evaluated the influence of carvacrol in the lipid matrix by Differential Scanning Calorimetry (DSC), Termogravimetry (TG), Small Angle X-ray Scattering (SAXS) and Polarized Light Microscopy (PLM). Inert and containing carvacrol NLCs were obtained by warm microemulsion method, and evaluated regarding the influence of lipid matrix and components concentration on the NLCs formation. NLCs were characterized by DSC and XRD as well. In addition, the in vitro carvacrol release from NLCs, the in vitro cytotoxicity assay, the in vitro promastigotes assay, the in vivo pharmacokinetics evaluation of free carvacrol and encapsulated were performed. Through the evaluation of influence of carvacrol on lipid matrix, it was possible to suggest that carvacrol may act also as a liquid lipid of NLCs formulation since TG, DSC, SAXS and PLM analysis that the lipid matrix became less ordered after adding carvacrol. Furthermore, DSC analysis showed that carvacrol was miscible in the tested concentration range. NLCs containing carvacrol were obtained successfully by warm microemulsion dilution method, being the NLCs formulation that presented the lowest particle size (98.42 ± 0.80 nm) and narrow size distribution (suitable for intravenous administration), the higher encapsulation efficiency, were those prepared using beeswax as solid lipid (HLB=9) and 5% of lipids and surfactant. The in vitro release of carvacrol from NLCs was fitted to Korsmeyer and Peppas, and Weibull model, demonstrating that the release mechanism is probably the Fickian diffusion type. Moreover, carvacrol encapsulation in NLCs provided a lower cytotoxicity in comparison to free carvacrol (p<0.05). However, carvacrol encapsulation in NLCs did not change its in vitro promastigotes efficacy. Finally, the in vivo pharmacokinetics of carvacrol after IV bolus administration suggests that this phenolic monoterpene undergo enterohepatic circulation and therefore presented a long half-life (t1/2) of 51.07 ± 2.80 h and low value of clearance (Cl) of 0.057 ± 0.003 L/h. In addition, C0, t1/2, mean residence time (MRT) and Vdss of encapsulated carvacrol were higher than free carvacrol (p < 0.05), favoring a higher distribution of carvacrol in the target tissues. Thus, it is possible to conclude that the developed NLCs are a promising delivery system for leishmaniasis treatment.